2019
DOI: 10.1186/s12962-019-0171-x
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to pay for social health insurance and its determinants among public servants in Mekelle City, Northern Ethiopia: a mixed methods study

Abstract: BackgroundOwing to lack of adequate healthcare financing, access to at least the basic health services is still a problem in Ethiopia. With the intention of raising funds and ensuring universal health coverage, a mandatory health insurance scheme has been introduced. The Community Based Health Insurance has been implemented in all regions of the country, while implementation of social health insurance was delayed mainly due to resistance from public servants. This study was, therefore, aimed to assess willingn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
69
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(95 citation statements)
references
References 14 publications
12
69
7
1
Order By: Relevance
“…Among the respondents who were willing to join the scheme, only one fourth were willing to pay less than or equals to 1%, and few respondents were willing to pay 1-2 % and 2-3% of their gross monthly salary. This finding is consistent with a study conducted in Mekelle city, Northern Ethiopia (17).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Among the respondents who were willing to join the scheme, only one fourth were willing to pay less than or equals to 1%, and few respondents were willing to pay 1-2 % and 2-3% of their gross monthly salary. This finding is consistent with a study conducted in Mekelle city, Northern Ethiopia (17).…”
Section: Discussionsupporting
confidence: 93%
“…In our case the study subjects were selected from different public servant groups with variable range of monthly income. On the other hand, the current finding is lower than studies conducted on government employees in Mekelle city, on teachers in Wolaita Sodo, on civil servants in Northwest Ethiopia, Kampala (Uganda), and Malaysia (9,10,(17)(18)(19)(20). Since awareness of the scheme drives for demand, this might be attributed to low awareness of the scheme in our study area.…”
Section: Discussioncontrasting
confidence: 68%
“…This is also evidenced from studies conducted among teachers in southern Ethiopia; which explains that teachers with higher educational status are more likely WTP for SHI (13). A higher educational status also showed a positive association with WTP in different studies conducted in Iran, Bangladesh, Nigeria, and Northern Ethiopia (14,18,20,21). Systematic review of WTP for health insurance in low and middle-income countries also indicated that the level of education affects WTP (7).…”
Section: Discussionmentioning
confidence: 99%
“…Data was collected using an interview questionnaire which was prepared by reviewing similar WTP studies and modified to fit the local context (8,11,(16)(17)(18)(19)(20)(21)(22). It was pretested among 10% of the sample size of the study participants, which were not included in the actual study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation